ANALISIS HUKUM ISLAM TENTANG ZAKAT HARTA ORANG YANG BERHUTANG - Zuhraini, Zuhraini; Firdaweri, Firdaweri (ASAS, 2020)
Islamic teachings are very complete, its teachings regulate all human problems including the problems of wealth which must be alms. Nowadays the problem of debt is the hottest issue for the people of Indonesia. Many people whose lives are inseparable from debt. The debt is used for consumptive purposes, daily living expenses and the debt is used for productive purposes, for business purposes and so on. It causes problems when connected with alms problems. This issue makes the researcher interested in analyzing it with the research title: “Analysis of Islamic Law Regarding The Alms of wealth for indebted people”. The formulation of the problems: 1. How is the analysis of Islamic law regarding the alms of the wealth of the debtor? Is the person who has a debt oblige or not oblige to pay alms? 2. Which should take precedence between paying debt and paying alms?. This research aims to find out as clearly as possible about the alms of wealth of those who are in debt. And to find out about things that must take precedence between paying alms and paying debt. This research is normative research which is descriptive. Data Collection of library research used analysis qualitative data. Based on the data and analysis, it can be concluded that: First, the Analysis of Islamic Law concerning the alms of the wealth of the debtor. If the debt is used for consumptive purposes, he is not obliged to pay alms, because his life needs are not fulfilled, the person is classified as poor, he is not including the rich who are obliged to pay alms. If debt is used for productive purposes, whose person borrows money for business purposes, it is not to cover basic needs but loans are used to add wealth. After being paid the debt due, his wealth is still up to senisab, he is obliged to pay alms. Second, It takes precedence between paying debts and alms. If someone faces two obligations at the same time, paying debt and alms, then he must first pay the debt and then pay the alms. Ajaran Islam sangat lengkap, mengatur seluruh permasalahan manusia.juga mengatur masalah harta yang wajib dizakatkan. Masa kini masalah hutang merupakan persoalan terhangat bagi masyarakat Indonesia. Banyak orang yang hidupnya tidak terlepas dari hutang. Baik hutang itu digunakan untuk kepentingan konsumtif, untuk biaya hidup sehari-hari, maupun hutang itu digunakan untuk kepentingan produktif, untuk kepentingan bisnis dan sebagainya. Sehingga menimbulkan masalah jika dihubungkan dengan masalah zakat. Permasalahan inipenting untuk diteliti, membuat peneliti tertarik untukmenganalisisnya dengan judul penelitian: “Analisis Hukum Islam Tentang Zakat Harta Orang yang Berhutang”.  Rumusan masalahnya: 1. Bagaimanakah analisis hukum Islam tentang zakat harta orang yang berhutang ?Apakah orang yang mempunyai hutang wajib atau tidak wajib membayar zakat ?.  2. Mana yang harus didahulukan antara bayar hutang dengan membayar zakat ?. Penelitian ini bertujuan untuk mengetahui sejelas mungkin,  tentang zakat harta orang yang berhutang. Dan untuk mengetahui tentang hal yang harus didahulukan antara bayar zakat dan bayar hutang. Penelitian ini termasuk penelitian hukum normative, yang bersifat deskriptif. Pengumpulan data library research,  dengan sistem analisis data kualitatif.  Berdasarkan data dan analisis yang dilakukan, disimpulkan bahwa: Pertama, Analisis Hukum Islam tentang zakat harta orang yang berhutang. Jika hutangnya digunakan untuk kepentingan konsumtif, iatidak wajib membayar zakat, karena keperluan hidupnya saja tidak terpenuhi, orang tersebut tergolong miskin, tidak termasuk orang kaya yang wajib mengeluarkan zakat. Jika hutang digunakan untuk keperluan produktif, dimana orang meminjam uang untuk kepentingan bisnis, bukan untuk menutupi kebutuhan pokok tetapi pinjaman digunakan untuk menambah kekayaan. Setelah dibayar hutangnya yang jatuh tempo, hartanya masih sampai senisab dia wajib membayar zakat.  Kedua,Hal yang harus di dahulukan antara bayar hutang dengan zakat. Jika seseorang menghadapi dua kewajiban pada waktu yang bersamaan yaitu membayar hutang danzakat, maka terlebih dahuluia harus membayar hutang kemudian baru membayar zakatnya,Kata Kunci : Hukum Islam, Zakat, Orang yang berhutang. Key words :Islamic law, alms, indebted person